Урахування гендерного аспекту як засобу підвищення ефективності правоохоронної діяльності - Твердохлєбова, Н. Є.; Tverdokhliebova, N. Ye. (Право і безпека. – 2017. – № 3 (66). – С. 149–153, 2017)
Проаналізовано специфічні проблеми інтеграції ґендеру в процес реформування поліцейських сил у сучасних умовах. Обґрунтовано необхідність створювати репрезентативні за кадровим складом інститути поліцейських сил. Сформульовано рекомендації щодо вдосконалення побудови правоохоронної системи, яка має передбачити оптимальне використання людського ресурсу для підвищення ефективності професійної діяльності правоохоронних органів.

The specific problems of gender integration into the process of reforming the police force in the present conditions have been analyzed. It has been determined that gender policy in the field of law enforcement should be aimed at ensuring balanced participation of women and men in decision-making, which will contribute to the formation of a new outlook on the role of women in the police, and thus, the promotion of gender equality. The author has revealed the main components of the formation and implementation of gender policy in Ukraine, which are the gender expertise, gender statistics, gender analysis, gender education and gender management. The necessity of creating representative staffing institutions of police force has been substantiated. The recommendations for improving the construction of law enforcement system, which should provide for optimal use of human resources for improving the efficiency of professional activities of law enforcement agencies, have been formulated. It has been determined that the importance of the formation and implementation of gender policy is primarily determined by the needs of social life, the need for the effective use of human potential of Ukraine as a European state and the development of each individual. Integration of the gender component into law enforcement activities is an important mean of strengthening the people’s confidence, increasing the country’s combat capability and strengthening the rule of law in the state.

Проанализированы специфические проблемы интеграции гендера в процесс реформирования полицейских сил в современных условиях. Обоснована необходимость создавать репрезентативные по кадровому составу институты полицейских сил. Сформулированы рекомендации по совершенствованию построения правоохранительной системы, которая должна предусмотреть оптимальное использование человеческого ресурса для повышения эффективности профессиональной деятельности правоохранительных органов.
Учёт гендерного аспекта как средства повышения эффективности правоохранительной деятельности
Taking into account the gender aspect as a mean of increasing the effectiveness of law enforcement activities
Твердохлєбова, Н. Є. Урахування гендерного аспекту як засобу підвищення ефективності правоохоронної діяльності / Н. Є. Твердохлєбова // Право і безпека. – 2017. – № 3 (66). – С. 149–153.
Tverdokhliebova, N.Ye. (2017), “Taking into account the gender aspect as a mean of increasing the effectiveness of law enforcement activities” [“Urakhuvannia hendernoho aspektu yak zasobu pidvyshchennia efektyvnosti pravookhoronnoi diialnosti”], Pravo i Bezpeka, No. 3, pp. 149–153.
Keywords: Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; гендер; ефективність професійної діяльності; гендерна експертиза; гендерна статистика; гендерний аналіз; гендерне навчання; правоохоронні органи; правоохранительные органы; law enforcement agencies; поліція; полиция; police; gender; efficiency of professional activity; gender expertise; gender statistics; gender analysis; gender education; личностные качества; гендерная экспертиза; гендерная статистика; гендерный анализ; гендерное обучение